(untitled) (Andamios, Revista de Investigación Social, 2013)
Using the first survey applied to certified as civil service servants at federal level in Mexico, this article looks to understand if a new administrative culture is already rising within this bureaucratic group. Mexican civil service is a young institution: its law was passed in 2003 after the dominant party that controlled the presidency for more than 70 years (PRI) lost it in 2000. The civil service law of 2003 aims to eliminate the spoils system and begins a new era for public administration. However, this law also assumes that a civil service is basically a problem of “professionalization” of individuals avoiding any attempt to see the civil service as a group of persons developing a group morale and ethos. This paper argues that an esprit de corps is an inevitable outcome of the maturity of a civil service, and the Mexican one will not be the exception.